Effect of chemical composition of aggregate on interfacial adhesion property between aggregate and asphalt. (15th August 2017) - Yin, Yanping; Chen, Huaxin; Kuang, Dongliang; Song, Lifang; Wang, Lu
Highlights: The adhesion strength between asphalt and limestone and granite aggregate are compared. The adhesion function of limestone may partly depend on its chemical bond. The adhesion strength of granite aggregate is highly dependent on its physical interface with asphalt. The sulfoxide group in the asphalt affects adhesion properties. Abstract: This study compared the interfacial adhesion properties of asphalt with limestone aggregate and asphalt with granite aggregate. The main chemical compositions of limestone and granite aggregate were analyzed using X-ray diffraction XRD. A dynamic shear rheometer (DSR) test was conducted to examine the rheological performance of the original asphalt, limestone-asphalt mortar, and granite-aggregate mortar. X-ray photoelectron spectroscopy (XPS) was applied to detect whether a chemical shift occurred between aggregate and asphalt, to analyze the adhesion function. The results show that the interfacial adhesion strength of the asphalt with limestone aggregate is higher than that of the asphalt with granite aggregate. The main chemical constituent of limestone is CaCO3, and the main chemical constituent of granite is SiO2 . Limestone-asphalt mortar samples and granite-asphalt mortar samples were prepared by mixing original asphalt with pure CaCO3 and SiO2 powders, respectively. The limestone-asphalt mortar has lower phase angle than the original asphalt, whereas the phase angle of granite-asphalt mortar differs slightly from that of original asphalt. Carbon, oxygen, and sulfur are the main elements of asphalt, and in particular, the sulfoxide group has an influence on the adhesion property of asphalt. The adhesion function of the limestone aggregate with asphalt may depend on the migration of the outermost orbital electrons of Ca 2+ to the active functional group in the asphalt, resulting in the formation of a new chemical bond. The adhesion function of the granite aggregate with asphalt is determined only in terms of its physical adhesion with the asphalt.